METHODS OF COOPERATIVE LEARNING AND THEIR APPLICATION IN THE DEVELOPMENT OF COMPETITIVE THEMES IN TEACHING MATHEMATICS - Ilic, Desa (Universitas Kuningan, 2018)
In modern school, children need to play a central role. It should become a place where they are exploring, examining, solving problems and to lead them to a deliberate dialogue. Students need to experience the school as a place where the child develops in cognitive, emotional and social sense, where the child's motivation to work is at a high level. An active school is more focused on a young man who is treated as a whole person whose intellectual potentials need to engage more in the teaching process. The active school is based on compulsory education standards based on which the orientation plans and work programs are designed. Such access also implies a part of teaching that is flexible and varies depending on the student's interest. In teaching, active learning methods are based on work and intellectual engagement of students and research activities. The goal of an active school is not only the adoption of a curriculum, but also the versatile personality development of students. The active school evaluates not only the degree of competence of the knowledge defined by the educational standards, but also the progress of the children in comparison with the initial situation, the motivation and interest of the students for work and activity, the development of the personality and the satisfaction of the student's teaching that is realized.Keywords: mathematics; learning; co-operation; classes.